Inner ear delivery: Challenges and opportunities - Szeto, Betsy (Laryngoscope Investig Otolaryngol, 2019)
OBJECTIVES: The treatment of inner ear disorders remains challenging due to anatomic barriers intrinsic to the bony labyrinth. The purpose of this review is to highlight recent advances and strategies for overcoming these barriers and to discuss promising future avenues for investigation. DATA SOURCES: The databases used were PubMed, EMBASE, and Web of Science. RESULTS: Although some studies aimed to improve systemic delivery using nanoparticle systems, the majority enhanced local delivery using hydrogels, nanoparticles, and microneedles. Developments in direct intracochlear delivery include intracochlear injection and intracochlear implants. CONCLUSIONS: In the absence of a systemic drug that targets only the inner ear, the best alternative is local delivery that harnesses a combination of new strategies to overcome anatomic barriers. The combination of microneedle technology with hydrogel and nanoparticle delivery is a promising area for future investigation. LEVEL OF EVIDENCE: NA